Analysis of Financial Feasibility of Tourism Transport and Shuttle Transport Business: (Case Study: PT. Penjor Bali Transport) - I Gede Fery Surya Tapa; I Nyoman Indra Kumara; I Nengah Darma Susila; I Ketut Sutapa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Before the Covid-19 pandemic, an increase in the number of foreign and domestic tourists. With the increase in the number of tourists, the number of tourist travel efforts to increase the mode of transportation, with the aim of travel and shuttle visits increases every year. The objectives of the study are to analyze most of the BOK of tourist and shuttle transportation, to analyze the revenue of financial transportation and shuttle transportation, and to analyze the feasibility of tourist and shuttle transportation. The data needed for this study are primary data obtained from questionnaire surveys and interviews, and secondary data obtained through related institutions. The total operational cost of the tourist transportation vehicle is Rp. 5,937,007,065 12 vehicles / year, shuttle transportation of Rp. 5,975,220,122 17 vehicles / year. The total tourism transportation revenue is Rp. 7,158,878,400 12 vehicles / year, and shuttle transportation of Rp. 8,978,130,221 17 vehicles / year. The financial feasibility of tourist transportation with an NPV value of Rp. 100,640,493,054> 0 (feasible), BCR value 1.95> 1 (feasible), IRR value 42.478%> 15% MARR (feasible), and PBP time of 7 years and 1 month. Shuttle transportation NPV value of Rp. 734,194,558> 0 (feasible), BCR value 1.02> 1 (feasible), IRR value 19.649%> 15% MARR (feasible), and PBP time of 6 years 4 months. Sensitivity analysis of tourist transportation costs increased by 34%, income decreased by 34% and shuttle costs increased by 1.5%, income decreased by 1.5%. Losses during 2020-2021, for tourist transportation amounted to -Rp. 10,782,606,379 12 vehicles / 2 years, shuttle transportation of -Rp. 16,866,802,314 17 vehicles / 2years